2017
DOI: 10.1016/j.yjmcc.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Uniform low-level dystrophin expression in the heart partially preserved cardiac function in an aged mouse model of Duchenne cardiomyopathy

Abstract: Dystrophin deficiency results in Duchenne cardiomyopathy, a primary cause of death in Duchenne muscular dystrophy (DMD). Gene therapy has shown great promise in ameliorating the cardiac phenotype in mouse models of DMD. However, it is not completely clear how much dystrophin is required to treat dystrophic heart disease. We and others have shown that mosaic dystrophin expression at the wild-type level, depending on the percentage of dystrophin positive cardiomyocytes, can either delay the onset of or fully pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Heterozygous mdx mice (expressing dystrophin in the heart at the level of ~50%) experience only mild cardiomyopathy, and cardiac muscle exhibits minor functional improvements with even as little as ~3% dystrophin expression . Further studies from our group suggest that therapeutic re‐introduction of ~15% of normal dystrophin in adult mdx mice is sufficient to provide protection against contractile damage …”
Section: Introductionmentioning
confidence: 91%
“…Heterozygous mdx mice (expressing dystrophin in the heart at the level of ~50%) experience only mild cardiomyopathy, and cardiac muscle exhibits minor functional improvements with even as little as ~3% dystrophin expression . Further studies from our group suggest that therapeutic re‐introduction of ~15% of normal dystrophin in adult mdx mice is sufficient to provide protection against contractile damage …”
Section: Introductionmentioning
confidence: 91%
“…On the other hand, studies on female mdx 3cv mice (B6 background), which carry a splicing-disruptive point mutation in Dmd intron 65 [ 83 ] and have ≈3.3% dystrophin of wild-type levels in the heart, revealed that uniform low-level dystrophin expression does not improve gross anatomical and histopathological features of the heart compared to female dystrophin-null mdx 4cv mice [ 75 ]. Mdx 4cv mice have a nonsense point mutation in Dmd exon 53, introducing a premature stop codon that prevents dystrophin synthesis [ 84 ].…”
Section: Cardiac Phenotypes Of Cellular and Female Animal Dystrophmentioning
confidence: 99%
“…A second point is that the expression pattern of dystrophin in the heart, and not just its level, appears to have a considerable impact on cardiac phenotype as well. Uniformly low dystrophin levels at 3.3% generally did not improve the cardiac phenotype in mdx 3cv mice, despite being near the 4% dystrophin level that was observed to ameliorate cardiac symptoms in mosaic models [ 75 ]. We have to recognize that although most cell and gene therapies for DMD have the same goal of increasing cardiac dystrophin levels, they may accomplish this by inducing different patterns of dystrophin expression in the heart.…”
Section: Implications For Therapy: How Much Dystrophin Is Enough Fmentioning
confidence: 99%
“…However, the expression of the therapeutic molecules must be high enough to correct the whole myotube. Some therapeutic effects may be observed with a low expression level (3%–5% of wild-type dystrophin expression for DMD treatment13, 14), but for some disorders, or to obtain more satisfying results, a higher level is needed (for DMD treatment, an estimated 20%–30% dystrophin expression level in 50% of fibers15, 16).…”
Section: Introductionmentioning
confidence: 99%